'Hotspot policing': a comparative analysis of sanctioned acts of policing versus media representations of policing in a stigmatized community in Trinidad. (1st November 2016) - Watson, Danielle
Abstract: The 'Partial State of Emergency' implemented in Trinidad and Tobago in August 2011, as well as media broadcasts on the crime situation, has brought to the forefront the high degree of interface between police officers and civilians within the identified 'hotspot communities'. The assumed realities of these individuals were communicated in such a manner which led to the stereotyping of citizens as marginalized victims and police officers as 'disrespectful bullies'. The media broadcasts reflected the act of policing as unitary, as opposed to encompassing a wide range of roles for interaction with civilians. These broadcasts revealed a high degree of violent physical displays by police officers, which were perceived as irrational, and in some instances inhumane. Despite community policing initiatives, there seem to be continued instances of problematic relations between police officers and civilians from 'hotspot communities'. The research examined the sanctioned responses of police officer governing interaction with civilians from one of these communities. It highlighted the extent to which these endorsed reactions are contextually portrayed in media footage. The study described the determinants governing police use of force as evidenced in the media with the aim of providing a direction for redress during interaction.